Koleksi surat kabar langka Perpustakaan Nasional Republik Indonesia sebagai sumber penelitian sejarah global - Frial Ramadhan Supratman (Universitas Padjadjaran, 2020)
Rare newspapers are one of the primary sources that can be used in historical research. Historians often use newspapers as a source of research. Therefore historians often come to the National Library of the Republic of Indonesia to conduct consultations on newspaper collections. Librarians should help historians find this main source. Thus, this research explains how the rare newspaper collection can be useful for historians in researching global history. The method used in this paper was descriptive qualitative. This method conducted a description and analysis to a research object, where the researcher a qualitative analysis of the research object. This study surveyed ten newspapers and sorted them into six papers, which were then analyzed. From the study results, the authors found that six rare newspapers in the National Library of the Republic of Indonesia could be used as a primary source in researching global history. The six papers were 'Oetoesan Hindia', 'Pancaran Warta', 'Keng Po', 'Warta Hindia', 'Pemandangan', and 'Soeara Oemoem.’ The conclusions of this research are; first, newspapers can be used as a primary source of global history because they contain writings that respond to global dynamics. Second, criteria for newspapers that can be used as a source of global history research are those that provide information and opinions on global developments.